2020
DOI: 10.1016/j.anai.2019.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short- and long-acting beta-agonists on asthma exacerbations: a prospective cohort

Abstract: Background. In asthma, short-and long-acting β-agonists (SABAs and LABAs) should be used together with inhaled corticosteroids (ICS), and regular use is inappropriate. Objective. To assess the relationship between patterns of use of therapy and asthma exacerbations (AEx). Methods. Asthmatic patients (6-40 years) were enrolled in France and the United Kingdom. Prescribing data, Computer-Assisted Telephone Interviews (CATIs), and text messages assessed medication use and AEx over a maximum period of 24 months. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…In line with our study, an association between SABA use and exacerbations has been found in several studies 26 , 27 . More conflicting evidence has been found about the association between ICS adherence and exacerbations.…”
Section: Discussionsupporting
confidence: 93%
“…In line with our study, an association between SABA use and exacerbations has been found in several studies 26 , 27 . More conflicting evidence has been found about the association between ICS adherence and exacerbations.…”
Section: Discussionsupporting
confidence: 93%
“…The SABA use IN Asthma (SABINA) program in adults and adolescents with asthma reported that SABA overuse (≥3 canisters/year) is prevalent in Sweden 17 and associated with poor asthma‐related outcomes 18,19 . Few studies have evaluated SABA use in the pediatric population or its impact on clinical outcomes 20–25 . Examining the extent of SABA collection and associated clinical outcomes in children across age groups and asthma phenotypes may provide further insights into reducing asthma morbidity in children.…”
Section: Introductionmentioning
confidence: 99%
“… 17 The difference between LABAs and ICS coverage rates has been identified previously, representing a risky situation, with some patients using LABAs as monotherapy, without the simultaneous use of ICS. 16 , 18 Of importance, this prescribing pattern has now virtually disappeared. 19 …”
Section: Discussionmentioning
confidence: 99%